(3JYdjb Ydi QSGdI HdhZ GdCQH aj JMbjb GSJYGQGJ GdYQHs - (3GdYdhqj GdMSfj GdeOfj GdSeQbfOj, CHh GdbGSe, eMeO Hf jhSa Hf eMeO (B556 (3g`s ((3YHO Gddg Hf HTjQ GdHhSJhjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfhCeG HYO agPG JYdjb bUOJ Hg Md eNJUQ aj GdehShe HHdhZ GdCQH aj JMbjb GSJYGQGJ GdYQHs
(3BNQgG (B:s
(3JQTjM ddGSJYGQI GdecfjI hef GdedGFejf ddeTHg aj Jdc JLQjO ddGSJYGQI GdeUQaI hGddg CYde HGdUhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 149s
(3eYLe GdeDdajf(B: 3 / 789s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdHdGZIs